Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/anie.201702570
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Stable ZnII–Oxyl Species Produced in an MFI Zeolite and Its Reversible Reactivity with O2 at Room Temperature

Abstract: Although a terminal oxyl species bound to certain metal ions is believed to be the intermediate for various oxidation reactions, such as O-O bond generation in photosystem II (PSII), such systems have not been characterized. Herein, we report a stable Zn -oxyl species induced by an MFI-type zeolite lattice and its reversible reactivity with O at room temperature. Its intriguing characteristics were confirmed by in situ spectroscopic studies in combination with quantum-chemical calculations, namely analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(87 citation statements)
references
References 31 publications
(9 reference statements)
12
75
0
Order By: Relevance
“…Oxyl bound to a Zn II ion has been recently identified in the zeolite catalyst. 27,28 Despite the poor ESR sensitivity due to the fast relaxation behavior, the Zn II −oxyl bond shows a vibronic progression that provides an electronic structure description of the Zn II −oxyl σ bond. 27,28 The oxyl electrophilicity was evidenced by a unique reversible reaction with O 2 via generation/decomposition of the side-on Zn II −ozonide species through the O−O radical coupling/decoupling mechanisms.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Oxyl bound to a Zn II ion has been recently identified in the zeolite catalyst. 27,28 Despite the poor ESR sensitivity due to the fast relaxation behavior, the Zn II −oxyl bond shows a vibronic progression that provides an electronic structure description of the Zn II −oxyl σ bond. 27,28 The oxyl electrophilicity was evidenced by a unique reversible reaction with O 2 via generation/decomposition of the side-on Zn II −ozonide species through the O−O radical coupling/decoupling mechanisms.…”
mentioning
confidence: 99%
“…27,28 Despite the poor ESR sensitivity due to the fast relaxation behavior, the Zn II −oxyl bond shows a vibronic progression that provides an electronic structure description of the Zn II −oxyl σ bond. 27,28 The oxyl electrophilicity was evidenced by a unique reversible reaction with O 2 via generation/decomposition of the side-on Zn II −ozonide species through the O−O radical coupling/decoupling mechanisms. 27,28 Considering the charge balance, it has been suggested that a monovalent ion-exchangeable site (Scheme 1, left) acts as the anchor site to constrain the monovalent Zn II −oxyl bond.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They also reported that the generated Zn II À O * species can oxidize methane (BDE C-H = 105 kcal/mol) to methanol, demonstrating extremely high HAA reactivity of the oxylcomplex of late-transition metal ions. [21] Moreover, Schwarz and co-workers demonstrated that NiO + (formally [Ni II À O * ] + ) is an efficient oxidant for methane hydroxylation in the gas phase reaction. [7] Judging from those reports, we propose that not only the aroyloxyl radical (ArC(O)O * ) but also (L)Ni II À O * species generated by the OÀ O homolysis of the nickel(II)-m-CPBA adduct a is a reactive oxidant in the catalytic alkane oxidation reaction is 1,1,3,3tetramethylguanidine.…”
Section: Nickel(ii)-oxyl ((L)ni II à O * )mentioning
confidence: 99%